2019
DOI: 10.15252/emmm.201809266
|View full text |Cite
|
Sign up to set email alerts
|

Apelin inhibition prevents resistance and metastasis associated with anti‐angiogenic therapy

Abstract: Angiogenesis is a hallmark of cancer, promoting growth and metastasis. Anti‐angiogenic treatment has limited efficacy due to therapy‐induced blood vessel alterations, often followed by local hypoxia, tumor adaptation, progression, and metastasis. It is therefore paramount to overcome therapy‐induced resistance. We show that Apelin inhibition potently remodels the tumor microenvironment, reducing angiogenesis, and effectively blunting tumor growth. Functionally, targeting Apelin improves vessel function and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 77 publications
6
81
0
Order By: Relevance
“…The results of our study fit with previous in vivo observations made, where ectopic apelin overexpression enhanced angiogenesis and tumor cell proliferation in subcutaneous tumor models [26,48,49]. Moreover, recent results obtained in a mouse model of breast cancer showed that loss-of-APLN markedly reduced tumor angiogenesis leading to impaired tumor growth and, consequently, improved survival of these animals [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study fit with previous in vivo observations made, where ectopic apelin overexpression enhanced angiogenesis and tumor cell proliferation in subcutaneous tumor models [26,48,49]. Moreover, recent results obtained in a mouse model of breast cancer showed that loss-of-APLN markedly reduced tumor angiogenesis leading to impaired tumor growth and, consequently, improved survival of these animals [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings demonstrated that endothelial cells do not respond to anti-VEGF therapeutics in the presence of activated apelin signaling. In parallel with our studies, other groups have shown that inhibition of the apelin/APJ pathway improves efficacy of established anti-angiogenic treatments in glioblastoma, and prevents the metastasis associated with anti-angiogenic therapy in breast carcinomas [41,42]. Importantly, we showed that in patients treated with bevacizumab, increased apelin expression correlated with worsened prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…The clinical outcome of targeting APLN/APLNR pathway for cancer therapy depends on the tumor type. In models of lung and breast cancer, targeting Apelin prevented resistance associated with anti-angiogenic therapy by reducing tumor growth, metastasis and improving vessel function [188]. In models of glioma, targeting Apelin promoted invasiveness of tumor cells positive for APLNR.…”
Section: Apelin/aplnr Pathwaymentioning
confidence: 99%